Review paperRecurrent aphthous stomatitis: genetic aspects of etiology - Ślebioda, Zuzanna; Szponar, Elżbieta; Kowalska, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Recurrent aphthous stomatitis (RAS; recurrent aphthous ulcers – RAU; canker sores) is a chronic inflammatory, ulcerative condition of the oral mucosa. Its prevalence in the general population ranges between 5% and 20%, depending on the method and group studied. The etiopathogenesis of the disease is considered to be multifactorial, but remains still not fully understood. In patients with RAS, an enhanced immunologic response occurs to some trigger factors that may include: mechanical injury, stress or bacterial and viral antigens. Higher prevalence of aphthae in relatives may also indicate the genetic background of the condition. The inheritance of some specific gene polymorphisms, especially those encoding proinflammatory cytokines, which play a role in the formation of aphthous ulcer, may predispose family members to RAS. The purpose of this paper was to present the main clinical features of recurrent aphthous stomatitis, epidemiologic data and crucial etiopathogenetic factors with a special emphasis on genetic background of the condition.